PEMUTIHAN GIGI: “WHEN IT’S NEEDED AND IT’S SAFELY OR NOT?” - RATIH VARIANI (JURNAL INFO KESEHATAN, 2014)
Teeth have an important role in our appearance, especially if we're smiling. If teeth become discolored, then we do not look beautiful smile again. The patient's desire to get a brighter smile and whiter teeth causing cosmetic care needs increase. One form of cosmetic dental services is teeth whitening. Teeth whitening is one way of overcoming the restoration of teeth discoloration discolored teeth back up close to the color of natural teeth through the repair process are chemically and aim to restore the patient's esthetic factor. However, not all cases of tooth whitening can be done. There are indications and contraindications for this treatment. Most people still think all the cases can be handled by this procedure. Indications and contraindications teeth whitening treatment is for patients with discoloration caused by aging, consumption of food, beverages, medications include tetracycline and fluorosis. While counter-indication is patients who are allergic to components of tooth whitening substance or material printed spoon, patients with very sensitive teeth, temporomandibular joints of patients with the disorder (TMJ), the patient was pregnant. Materials used for teeth whitening procedures, categorized into 2:Materials containing peroxide bleach and toothpaste containing bleach. Whitening procedure can be performed in the clinic and at home, but still in the dentist's supervision. For content security levels of hydrogen peroxide/carbamide peroxide (for maintenance procedures in clinics around 15-38%, while for home care around 3-10%). Nevertheless, this teeth whitening side effects that often occur sensisitivitas irritation of the gums and soft tissues like gums. It is therefore recommended after the treatment is done to reduce the application flour to a sense of pain and remineralization process.